The interpretation of protoplanetary disc wind diagnostic lines from X-ray photoevaporation and analytical MHD models - Weber, Michael L.; Ercolano, Barbara; Picogna, Giovanni; Hartmann, Lee; Rodenkirch, Peter (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. High-resolution spectra of typical wind diagnostics ([O i] 6300 Å and other forbidden emission lines) can often be decomposed into multiple component
Gesehen am 17.09.2020